Research in the social scientific study of religion - Village, Andrew; Hood, Ralph W. Jr. 1942- (Brill, 2017)
This volume of Research in the Social Scientific Study of Religion includes a wide range of papers from a social-science perspective. The special section gives a unique insight into the rapidly growing field of psychological studies of religion in China. It draws on experts from China and the USA who met for a conference at Fuller Theological Seminary and have together compiled a collection of original research and reviews that helps to locate the current state of the discipline from a specifically Chinese perspective. Other papers in the volume examine intergenerational religious transmission and religious problem-solving styles in the USA.
Keywords: Religionssoziologie; Aufsatzsammlung